Circular Economy in The Leather Industry: A Comprehensive Review of Solid Waste Management Methods And Technologies - Gabriela ZIELINSKA (Communications of International Proceedings, 2025)
The article presents the issues related to solid waste generated by the leather industry and the developed methods of their management, aiming to reduce the negative impact of waste on the environment. Despite numerous data regarding the annual production volume of leather in tanneries worldwide, the literature lacks comprehensive analyses concerning the degree of reuse of leather waste generated during production. This data represents an essential element that enables the assessment of the effectiveness and efficiency of implementing a closed-loop resource utilization model in the leather sector. The article employs a systematic literature review methodology to gather data on the percentage of solid waste repurposed in tanneries around the world. The analysis of the problem allowed for the formulation of the conclusion that, despite the undertaken initiatives, research, and projects, the degree of utilization of solid leather waste in most countries around the world remains low. Therefore, there is a necessity to conduct research and implement methods that ensure the maximum possible utilization of leather wast
Keywords: Leather; leather industry; circular economy; solid waste management